Patients’ experience with received healthcare in internal medicine and surgery wards of Slovenian hospitals - Skela-Savič, Brigita (Zdravstveno varstvo, 2025)
Aim: The aim of the study was to explore the experiences of patients with delivered healthcare in selected Slovenian hospitals. Methods: A cross-sectional study was employed. A total of 1,748 patients participated. A shortened version of the Consumer Assessment of Healthcare Providers and Systems survey was used. Permission to conduct the study was obtained from the Slovenian Medical Ethics Committee. Data were collected between February and March 2020. Univariate, bivariate and multivariate analyses were conducted. Results: The average hospital rating was 8.86 (SD=1.47; p<0.001) out of 10. The hospital would be definitely recommended to others by 1,290 (75.7%) respondents. The regression model “patients’ experience with care” was explained in 18%, mostly by “patients’ general health status” (-0.267), “provision of written and oral information about symptoms or health problems post discharge” (-0.200), and “talking to patients about care post discharge” (-0.175). The model “hospital rate” was explained in 30.4% by “patients’ experience with care” (0.576), “new medication was explained” (-0.242) and “patient age” (0.132). Conclusion: The hospital rates are good and mostly explained by patient experience. The results revealed that tasks connected to comprehensive preparation of patients for healthcare treatment including communication, health education and appropriate discharge are only partially fulfilled. Improvements and holistic data capture are needed to make the measurement of patient experience a greater contribution to the improvement and efficiency of hospital care.
Keywords: bolnišnično okolje; discharge; doctors; hospital environment; information; informiranje; izkušnje; medicinske sestre; nurses; odpusti; patient needs; potrebe pacientov; satisfaction; zdravniki